Effectiveness of Cue-Exposure Therapy on Alcohol Craving in Virtual Environment: Based on habit loop - Alireza Karimpour Vazifehkhorani; Arina Attaran; Azizeh Karimi Saraskandrud; Haniyeh Faghih; Narges Yeganeh (Addiction and Health, 2022)
Background: In the treatment and abstinence of alcoholism, especially in abstinence after treatment, "Craving" has an essential role. Thus, our aim was to examine the effect of cue-exposure therapy on alcohol craving in virtual environment based on the habit loop.Methods: The present investigation was a case-control experimental study with a pretest–posttest–5 weeks follow–up design. Research population were alcohol-addicted people hospitalized in a psychiatric hospital. We had 62 subjects who had abstained from alcohol consumption. The sampling method was convenience sampling and the sample allocation was randomized and matched. The intervention was VR-CET that was implemented in eight sessions. Penn Alcohol Craving Scale, Alcohol Urge Questionnaire, and Obsessive Compulsive Drinking Scale were used to collect the data. In order to analyze the data, analysis of covariance (ANCOVA) in SPSS V.23 was performed.Findings: Our results showed that after implementation of VR-CET program the rate of PACS reduced significantly in posttest stage (p = 0.01) and follow up stage (p= 0.05). Also, the rate of AUQ and OCDS after exposure to VR-CET program declined significantly. The significant level of AUQ and OCDS in posttest and follow up stages were set at p- value < 0.01 and p-value <0.05 respectively.Conclusion: VR-CET program can reduce alcohol craving by paying attention to various cues and contexts. In fact, it would be more beneficial if the treatment environment resembles a conditioned context and contains as many related cues as possible.